Efficacy of passive ultrasonic irrigation with natural irrigants (Morinda citrifolia juice, Aloe Vera and Propolis) in comparison with 1% sodium hypochlorite for removal of E. faecalis biofilm: An in vitro study - Anuj Bhardwaj; Natanasabapathy Velmurugan; Sumitha; Suma Ballal (Wolters Kluwer Medknow Publications, 2013)
Aim: Present study evaluated the efficacy of natural derivative irrigants, Morinda citrifolia juice (MCJ), Aloe Vera and Propolis in comparison to 1% sodium hypochlorite with passive ultrasonic irrigation for removal of the intraradicular E. faecalis biofilms in extracted single rooted human permanent teeth. Materials and Methods: Biofilms of E. faecalis were grown on the prepared root canal walls of 60 standardized root halves which were longitudinally sectioned. These root halves were re-approximated and the samples were divided into five groups of twelve each. The groups were, Group A (1% NaOCl), Group B (MCJ), Group C (Aloe vera), Group D (Propolis) and Group E (Saline). These groups were treated with passive ultrasonic irrigation (PUI) along with the respective irrigants. The root halves were processed for scanning electron microscopy. Three images (X2.5), coronal, middle and apical, were taken for the twelve root halves in each of the five groups. The images were randomized and biofilm coverage assessed independently by three calibrated examiners, using a four-point scoring system. Results: 1% NaOCl with passive ultrasonic irrigation (PUI) was effective in completely removing E. faecalis biofilm and was superior to the natural irrigants like MCJ, Aloe vera and Propolis tested in this study. Conclusion: 1% NaOCl used along with passive ultrasonic irrigation was effective in completely removing E. faecalis biofilm when compared to natural irrigants (MCJ, Aloe Vera and Propolis).